Study of The Shift in The Function from Religious Education to Rehabilitation: Pesantren Al-Jannatu DÄrul Ma'wa Condromowo Ngawi - Fuadi , Moh. Ashif; Arisandi , Bustomi (LPPPM STAI Darul Hikmah Bangkalan, 2022)
Pesantren also accompanied the beginning of the journey and development of Islam. As an educational institution that breathes Islam, Pesantren can grow and develop. In this study, the author chose Pesantren al-Jannatu DÄrul Maâ€™wa Condromowo as the subject of the study. Pesantren Condromowois a Salaf Pesantren that focuses its attention on people who have mental illness in addition to continuing to teach religious sciences. This study aims to see the process of shifting the function of pesantren, what context is behind the change in function, and how the implications of changing the function of pesantren. This research uses historical research methods with stages of topic selection, heuristics, verification, interpretation, and historiography. The historical analysis is supported by literature studies, interviews, and observations. This result shows that several things background the development and changes of Pesantren. In the external context of the changes that occur in the case of increasing the percentage of mentally ill students every year, the impact of modernization, and the view that pesantren is a place of treatment for alternative In the internal context, change occurs due to the science and attitude of the Kiai in responding to the changes that occur. The implication is that there is a new typology in the world of pesantren, namely Pesantren Rehabilitation.